A Facile Approach to Bis(isoxazoles), Promising Ligands of the AMPA Receptor - Dmitry A. Vasilenko (MDPI AG, 2021)
A convenient synthetic approach to novel functionalized bis(isoxazoles), the promising bivalent ligands of the AMPA receptor, was elaborated. It was based on the heterocyclization reactions of readily available electrophilic alkenes with the tetranitromethane-triethylamine complex. The structural diversity of the synthesized compounds was demonstrated. In the electrophysiological experiments using the patch clamp technique on Purkinje neurons, the compound 1,4-phenylenedi(methylene)bis(5-aminoisoxazole-3-carboxylate) was shown to be highly potent positive modulator of the AMPA receptor, potentiating kainate-induced currents up to 70% at 10−11 M.